Pinto Liberty, new variety of bean for the state of Durango - Rosales Serna, Rigoberto; Ibarra Pérez, Francisco Javier; Cuéllar Robles, Evenor Idilio (Revista Mexicana de Ciencias Agrícolas, 2018)
The bean (Phaseolus vulgaris L.) of pinto grain and large size (35-45 g/100 seeds) is appreciated by producers, traders and packers in Mexico. In Durango, the producers demanded early varieties, tolerant to darkening of the seed coat and seed size larger than that of Pinto Saltillo, currently considered as a reference of quality. The objective was to develop a superior variety to Pinto Saltillo in earliness, grain size and commercial quality. The variety Pinto Liberty (PT08035) was generated in INIFAP-Durango, with the pedigree method, applied to the cross Pinto Mestizo / Pinto Saltillo-69-2-1. The average yield of Pinto Liberty was 983 kg ha-1 and ranged from 89 kg ha-1 up to 2 006 kg ha-1. Pinto Liberty compared with Pinto Saltillo, resulted early to maturity (91 vs. 95 days) and registered higher weight of 100 seeds (38 g vs. 31 g). The growth habit of Pinto Liberty is of an indeterminate vine, with short non-climbing guides, the average canopy height is 32 cm and a growing guide of 79 cm. The Pinto Liberty bean is medium to large size and its weight f luctuates between 33 and 49 g/100 seeds, is has an elliptical form in its cross sections and longitudinal, the seed coat is cream-colored, brown strips and a yellow hilum. In the field, Pinto Liberty showed tolerance to anthracnose and rust, as well as intermediate susceptibility to common blight and root rots. Pinto Liberty was included in validation programs to assess its possibilities of adoption, adaptability and potential to increase the quality of beans produced in the highlands of Mexico.
Keywords: Phaseolus vulgaris L.; quality; marketing; yield